A new pit viper of the genus Trimeresurus (Lacépède, 1804) (Squamata: Viperidae) from Southwest China - Chen, Zening; Yu, Jianping; Vogel, Gernot; Shi, Shengchao; Song, Zhaobin; Tang, Yezhong; Yang, Jia; Ding, Li; Chen, Cangsong (Zootaxa, 2020)
The white-lipped tree viper, Trimeresurus albolabris Gray, is one of the most common species of the genus Trimeresurus with a wide distribution from India eastwards to China and southwards to Indonesia. However, this species was previously split into five geographical clades with significant genetic divergence. Recent surveys in Yingjiang County, Yunnan Province, China resulted in the discovery of one cryptic species of the subgenus Trimeresurus. Combining molecular, morphological and ecological data, we describe it as a new species Trimeresurus caudornatus sp. nov. The new species differs from other Trimeresurus species by a combination of the following characteristics: (1) Head and body generally dark green, postocular stripes absent in both genders, upper labials light green; (2) ventrolateral stripe faint green yellow, present on the first row of DSR in both genders; (3) iris golden yellow in both genders; (4) dorsal tail mostly dark red, lateral and ventral green; an orange red stripe along the ventral part of the tail; (5) DSR 21/22 –21–15, VEN 161–163, SC 52–72; (6) first upper labial partially fused to the nasal. The new species was shown to be a strongly supported monophyletic group (BPP 100%) and sister to T. septentrionalis. The uncorrected pairwise distances of mitochondrial gene Cytb between the new species and other species of the subgenus Trimeresurus, ranging from 0.059 (T. septentrionalis) to 0.134 (T. kanburiensis).